Implementasi Media Flash Card Dalam Meningkatkan Penguasaan Kosakata Bahasa Arab - Miftakhul Falah Islami; Miftakhul Falah Islami (Muhamadiyah, 2018)
This study aims to determine the implementation of flash card media in improving Arabic vocabulary mastery. This research is included in classroom action research. The subjects of this study were students of class X IIS 2 Muhammadiyah 5 High School in Yogyakarta academic year 2017/2018. The method used to collect data is observation, tests, documentation, and field notes. The results showed an increase in vocabulary mastery after the use of flash card as a learning medium. The increase can be seen from the pre-test value and the post-test value. The average value of the first cycle class between pre test and post test showed an increase in value of 48 points from the average grade of 30 points in the pre test to 78 points in the test post. so that it can be seen that there is an increase in Arabic vocabulary mastery before and after the action. The increase has not been significant because the average grade is still below the indicator of success. And the average grade in the second cycle between pre-test and post-test shows an increase in value of 70 points from the average grade of 15 points in the pre-test to 85 points in the post-test value. Keywords: Media Flash Card, Arabic Vocabulary